Constructing Applied Knowledge in Nursing Students: A Learning Experience Centered on Evidence-Based Practice. - García-Expósito, Judith; Tort-Nasarre, Glòria; Torné-Ruiz, Alba; Roca, Judith; Esqué, Sara; Sanromà-Ortíz, Montserrat (Nursing Reports, 2025)
Background: Evidence-based practice must be promoted in nursing education to provide quality care. For this, teaching practices that promote its development must be considered. Aim: The aim of this study was to explore a learning experience centered on evidence-based practice through cooperative learning in an online discussion forum with nursing students. Methods: We employed a descriptive qualitative study with the participation of 137 nursing students. A teaching intervention based on cooperative teamwork through an online forum is proposed. The students, through a question, must manage information to provide a reasoned answer. The interactions in the forums were analyzed through qualitative content analysis. Results: Two themes and eight categories emerged: Critical Analysis of the Literature (Computer Literacy, Reliability of the data sources, Level of evidence according to the article design, and Relevance of the research) and Clinical Practice (Patient's perspective, Professional experience, Quality of care, and Usefulness of EBP). Conclusions: The use of interactive teaching methodologies (cooperative learning and online discussion forums) facilitates the construction of knowledge applied to clinical practice. Students perceive EBP as necessary and useful for optimal care management, and the forums allow for the development of key competencies, such as autonomous learning, teamwork, and critical thinking.